(untitled) - Carle, Eric; DeGennaro, Gabriella (New York, New York, 2025)
Look for various vegetables on each spread with The Very Hungry Caterpillar.
Ages 1-3.
Keywords: Fiction; Counting; Fiction; Gardens; Fiction; Vegetables; Fiction; Counting; Juvenile fiction; Juvenile fiction; Gardens; Juvenile fiction; Vegetables; Juvenile fiction; Caterpillars; Caterpillars; Picture puzzles; Board books